Ligilactobacillus agilis W70: a probiotic with capacity to enhance ammonia assimilation in the rumen - Duan, Xiaowei; Vigors, Stafford; Ma, Rui; Ma, Lu; Gu, Jingang; Bu, Dengpan (Frontiers in Microbiology, 2025)
Ruminants excrete both undigested and excess consumed nitrogen (N) through feces and urine, which results in the waste of feed protein and environmental pollution. This study aims to screen bacteria to identify strains with potential to improve nitrogen utilization in the rumen. In a tube screening test, when 30 mmol/L ammonium sulfate was added as the only nitrogen source in liquid medium, among 115 bacterial strains belonging to Bacillus and lactic-acid bacteria, 10 strains with the highest growth (OD600nm level) in comparison to the other evaluated strains were identified, and of these, Ligilactobacillus agilis W70 and Limosilactobacillus fermentum M50, had the highest ammonia nitrogen utilizing capabilities of ammonium sulfate (32.09 and 40.64%, respectively). A subsequent in vitro fermentation experiment was conducted with the diet consisting of 0.5 g TMR, 50 mL buffer solution, and 25 mL fresh rumen fluid per serum bottle which was incubated at 39°C for 24 h. The experiment consisted of 3 treatments, CTL, L. agilis W70 (1 × 109 cfu/mL), and L. fermentum M50 (1 × 109 cfu/mL), each treatment had 6 replicates, repeated across 3 batches. The addition of L. agilis W70 decreased NH3N (p < 0.01), the ratio of acetate to propionate (A:P) (p < 0.01), and increased the yields of microbial protein (MCP) (p < 0.01) and enzymatic activities of glutamate dehydrogenase (GDH) (p < 0.05) and glutamine synthetase (GS) (p < 0.05). Further genome analysis revealed that the L. agilis W70 harbors the glutamate dehydrogenase and glutamine synthetase-encoding genes gdhA and glnA that play key roles in ammonia utilization. This study identified L. agilis W70 as a strain which exhibits high NH3N utilization capability and enhances ammonia assimilation in vitro. The strain was further characterized to elucidate this ammonia assimilation potential. Further studies will be conducted to develop strain L. agilis W70 as a new feed additive to improve the nitrogen utilization efficiency in ruminant animals.